Analisis Peningkatan Ketahanan Sobek pada Karton Ivory Laminasi Doff dan Laminasi Glossy - Septia Ardiani; Meuthia Suryani; Nurul Akmalia (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
One of the commonly used food packaging materials is cardboard. Cardboard was chosen because it has several advantages including light weight, inexpensive, easy to form, easy to print, easy to store and easy to recycle. However, it tears more easily than other packaging materials such as plastic, cans, and glass. Lamination is done to increase the ketahanan sobek value. The type of folding cardboard that is commonly used as a food packaging material is ivory. In this test, the density of ivory is 260 gsm and 310 gsm. There were three types of ivory tested, namely non-laminated, doff laminated, and glossy laminated. This study aims to analyze the comparison of ketahanan sobek values of laminated ivory and non-laminated. The methods used in testing are ISO 534:2011, ISO 536:2010, and ISO 1974:2012. The results showed that the increase in the ketahanan sobek value of cardboard was 22% -24% for doff lamination and 24% -26% for glossy lamination.